Implementing diversity, equity, inclusion, and belonging management in organizational change initiatives - El-Amin, Abeni, 1974- (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"This edited book highlights research on a variety of business topics such as diversity, equity, inclusion, and belonging (DEIB), change management, collaborative leadership, DEIB leadership, organizational development, organizational leadership, strategic management, shared leadership, and stakeholder development"--